2014
DOI: 10.1007/s00270-014-1047-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stroke and Obstruction of the Extracranial Carotid Artery Combined with Intracranial Tandem Occlusion: Results of Interventional Revascularization

Abstract: Endovascular recanalization of acute cervical carotid artery occlusion was technically feasible in all patients, and resulted in high extra- and intracranial revascularization rates. A trend for favorable clinical outcome was seen in a higher TICI score, younger age, good collateral status, and combined IV rTPA and endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
2
51
0
1
Order By: Relevance
“…Nowadays, in most centres, i.v aspirin is advised promptly and double antiplatelet treatment on the following days in patient wall stents is applied. 8,9 Atrial fibrillation The most frequent reason resulting in an ICA pseudo-occlusion appearance in our study group was AF, which was observed in five patients. We realized that different locations of occlusion may give rise to the pseudo-occlusion appearance in the AF group.…”
Section: Ethical Approvalmentioning
confidence: 79%
See 1 more Smart Citation
“…Nowadays, in most centres, i.v aspirin is advised promptly and double antiplatelet treatment on the following days in patient wall stents is applied. 8,9 Atrial fibrillation The most frequent reason resulting in an ICA pseudo-occlusion appearance in our study group was AF, which was observed in five patients. We realized that different locations of occlusion may give rise to the pseudo-occlusion appearance in the AF group.…”
Section: Ethical Approvalmentioning
confidence: 79%
“…aspirin for the initial treatment followed by a double antiplatelet regime. 8,9 In all these applications, although haemorrhage is the most feared outcome, acute thrombosis of the stent could occur. Acute thrombosis of stents, generating a high-grade stenosis, can give rise to tandem occlusions and present as a CT pseudo-occlusion.…”
Section: Cervical Internal Carotid Artery Dissectionmentioning
confidence: 99%
“…28 Recently published cohort studies indicate that tandem stenosis/occlusions of the ICA/MCA can be treated with acute stenting of the extracranial internal carotid and stent retriever mechanical thrombectomy in the MCA with a reasonable risk profile. [29][30][31][32][33] However, further evaluation of this treatment strategy is warranted.…”
Section: Aspects To Be Considered In Mechanical Thrombectomymentioning
confidence: 99%
“…Others are caused by extracranial occlusions. Second, the underlying etiologies of ICA occlusion are too complicated to make an accurate judgment of the lesion pattern such as atherosclerosis, thromboembolic or artery dissection [34]. Third, the original size of the clots is usually larger in ICA than that of those ending up in the MCA.…”
Section: Possible Factors Influencing the Outcomes Of Stroke From Carmentioning
confidence: 99%